MULTILEVEL DRAINAGE OF BILE DUCTS IN OBSTRUCTIVE JAUNDICE AND CHOLANGITIS - N. E. Zarkua (Вестник хирургии имени И.И. Грекова)
The data of combined application of low invasive intervention on bilious tree were analyzed in 63 patients with the obstructive jaundice and cholangitis. An indication for operation and the option of performing multilevel drainage were validated in patients with the obstruction of bile-excreting system and cholangitis. The technique of percutaneous intraluminal biopsy of hepaticocholedoch with atherectomic camera was supposed. The data obtained allow the application of given approach during the treatment of patients with the severe stage of the disease.